Increased severe primary graft dysfunction in left ventricular assist device patients following united network for organ sharing allocation changes. Issue 1 (25th November 2022) - Guo, Aaron; Kotkar, Kunal; Jocher, Brandon; Botkin, Kent W.; Britt, Daniel; Fischer, Irene; Masood, Muhammad F.; Schilling, Joel; Itoh, Akinobu
Abstract: Introduction: In 2018, the United Network for Organ Sharing (UNOS) implemented a new heart allocation system which prioritized patients on temporary support devices and left‐ventricular assist device (LVAD) patients with complications. These changes have the potential to impact outcomes for patients bridged to transplant with an LVAD. Methods: We performed a retrospective study of 168 adult heart transplant recipients at our center between 2016 and 2020 evaluating post‐transplant outcomes before and after UNOS allocation changes. Donor and recipient data were retrieved from chart review and national databases. The primary outcome of this study was severe primary graft dysfunction (PGD) with secondary outcomes of 30‐day readmission, 30‐day mortality, and 1‐year mortality. Results: Incidence of severe PGD was similar in the overall cohort before and after the changes (10% vs. 15%, respectively, p  = .3) and increased in the LVAD‐bridged cohort (12% vs. 40%, respectively, p  < .01). Secondary outcomes of readmission and survival were similar between all groups. Blood transfusion was predictive of severe PGD in multivariable modeling (OR 1.3 [1.11–1.59], p  < .01).